On the Potential Role of the Neural Crest Cells in Integrating Pigmentation Into Behavioral and Physiological Syndromes - San-Jose, Luis M.; Roulin, Alexandre (Frontiers in Ecology and Evolution, 2020)
Melanin pigments colour the integument of vertebrates with shades of rufous, grey, and black. In numerous wild species, melanin-based colouration associates to different behavioural, physiological, and morphological traits, yet the proximate basis of such associations remains largely unknown. The neural crest/domestication syndrome hypothesis (Wilkins et al. 2014) proposes that correlated changes in pigmentary, behavioural, physiological, and morphological traits of domestic species result from deficiencies affecting the number or development of neural crest cells in the embryo. Here, we review to what extent the neural crest cells might also explain the associations observed between melanin-based colouration and distinct traits in wild vertebrate populations. Genes involved in the development of the neural crest explain colour differences in some vertebrate species, particularly, in cichlid fishes. Cells that originate from the embryo’s neural crest cells play functions that have been previously associated with melanin-based colouration in wild vertebrates and we propose the potential mechanisms through which the association of melanin-based colouration with other traits can be the consequence of having a common origin at the neural crest cells. We encourage considering the influence of the neural crest as a new avenue of research, integrating developmental biology and evolutionary ecology to better understand why and how melanin-based colouration of vertebrates become associated to multiple phenotypic aspects.